(untitled) (Swiss Medical Weekly, 2026)
OBJECTIVE: To quantify the number and proportion of retracted publications across 131 high-impact medical journals spanning nine clinical disciplines and to compare retraction rates and the proportion of misconduct-related retractions across journals and disciplines. METHODS: This cross-sectional study analysed all retracted publications in 131 top-ranked journals (15 per discipline) in anaesthesiology, dermatology, general internal medicine, gynaecology/obstetrics, neurology, oncology, paediatrics, psychiatry and radiology. Journals were selected using the 2023 Journal Impact Factor from Clarivate’s Journal Citation Reports. Retractions were identified in the Retraction Watch Database (RWD), PubMed and the Web of Science from journal inception to 15 December 2024. Retraction rates per 1000 publications were calculated using total publication output indexed in PubMed. The proportion of misconduct-related retractions was determined based on the RWD classification. RESULTS: 878 retracted publications have been identified among 422,827 publications in total, corresponding to a retraction rate of 2.1 per 1000. Among the 811 retractions with available data on reasons, 542 (66.8%) were attributed to misconduct. Retraction rates and the proportion of misconduct-related retractions varied widely across disciplines. Anaesthesiology accounted for the highest retraction rate (7.0 per 1000) and the highest proportion of misconduct-related retractions (88.9%). All authors with ≥20 retracted articles were anaesthetists based in Japan or Germany. CONCLUSION: Retractions and misconduct-related retractions are unevenly distributed across disciplines. These findings underscore the importance of strengthening editorial oversight and promoting research integrity.